Rancangan Teknik Reklamasi Penambangan Pasir dan Batu Di Dusun Banaran, Desa Keningar, Kec. Dukun, Kab. Magelang, Jawa Tengah - rizaldi ramadhan nasution; Agus Bambang Irawan; Ekha Yogafanny (Jurusan Teknik Lingkungan, FTM, Universitas Pembangunan Nasional “Veteran” Yogyakarta, 2020)
The research was conducted in Banaran Hamlet, Keningar Village, Dukun Subdistrict, Magelang District, Central Java, which is a mining area for sand and rock, previously the area was a private forest. Mining system used in the form of open pit mining and traditional mining methods. The purpose of this research is to determine the level of land and the technical design of mine reclamation mining areas at the study site.The methods used in this research was field survey, mapping and descriptive analysis. The sampling technique used in this research was purposive sampling technique which is a part of non-probability sampling. Descriptive analysis was based on the Environment Ministerial Decree Number 43 of 1996 concerning Standards Criteria for Environmental Damage for Group C mining Businesses and Activities on Land and DIY Governor Decree Number 63 of 2003.Based on the research report, the mining area fulfills the damaged criteria because out of all the tested parameters, only 1 parameter fulfills the good criteria. No management of topsoil, the base relief excavation is more than 1 meter, the average wall slope is 55o (142,81%), the height of the excavation wall with an average of ±5,6 meters and land cover/vegetation reaching 33,35%. The technical design will be used is making bench terraces and making drainage channels. The plants used as revegetation are sengon, jackfruit and vetiver grass as cover crop plants. Keywords: Sand and Rock Mining, Land Degradation, Soil Fertility, Reclamation